Okra for aesthetic beauty - John, K. Joseph; Latha, M.; Scaria, Sheen; V.A., Muhammed Nissar; Dwivedi, N. K.; Bhot, K. V. (Indian Horticulture, 2019)
The hybrid of okra resembles to that of shoe flower (Hibiscus rosa sinensis) but it is superior in appearance due to dwarf stature, large-sized flowers and folded umbrella like appearance of fully-grown buds. It is easy to cultivate and harvest. Its compact branches with green foliages and contrasting large showy red flowers are a feast to the eyes. Easy propagation through soft wood and semi-hard wood cuttings is ideal for establishment. Further, it can be used in flower arrangements, for garland-making and as a bed or potted plant for landscaping.